Modeling interaction between gp120 HIV protein and CCR5 receptor. (24th January 2019) - Guryanov, I.; Real‐Fernández, F.; Sabatino, G.; Prisco, N.; Korzhikov‐Vlakh, V.; Biondi, B.; Papini, A.M.; Korzhikova‐Vlakh, E.; Rovero, P.; Tennikova, T.
Abstract : The study of the process of HIV entry into the host cell and the creation of biomimetic nanosystems that are able to selectively bind viral particles and proteins is a high priority research area for the development of novel diagnostic tools and treatment of HIV infection. Recently, we described multilayer nanoparticles (nanotraps) with heparin surface and cationic peptides comprising the N‐terminal tail (Nt) and the second extracellular loop (ECL2) of CCR5 receptor, which could bind with high affinity some inflammatory chemokines, in particular, Rantes. Because of the similarity of the binding determinants in CCR5 structure, both for chemokines and gp120 HIV protein, here we expand this approach to the study of the interactions of these biomimetic nanosystems and their components with the peptide representing the V3 loop of the activated form of gp120. According to surface plasmon resonance results, a conformational rearrangement is involved in the process of V3 and CCR5 fragments binding. As in the case of Rantes, ECL2 peptide showed much higher affinity to V3 peptide than Nt (KD = 3.72 × 10 −8 and 1.10 × 10 −6 M, respectively). Heparin‐covered nanoparticles bearing CCR5 peptides effectively bound V3 as well. The presence of both heparin and the peptides in the structure of the nanotraps was shown to be crucial for the interaction with the V3 loop. Thus, short cationic peptides ECL2 and Nt proved to be excellent candidates for the design of CCR5 receptor mimetics. Abstract : Cationic peptides comprising N‐terminal tail (Nt) and second extracellular loop (ECL2) of CCR5 receptor, bind with high affinity the peptide representing V3 loop of HIV gp120 (KD = 0.04 μM and 1.10 μM, respectively). Heparin‐covered nanoparticles (nanotraps) bearing these CCR5 peptides effectively bind V3 as well. The presence of both heparin and peptides in the structure of the nanotraps is shown to be crucial for the interaction with V3 peptide.